Bring your whole self into work, keep your whole self out - Eustace, Alan (My University, 2025)
The theme of this special issue assumes a dichotomy between employees’ free speech and employers’ business interests. It comes as no surprise to labour lawyers to find the interests of employees and employers in tension, even fundamental conflict. But despite oceans of ink spilled in scholarship and media about ‘safe spaces’ and ‘cancel culture’, the nature and scope of this dichotomy remains underdefined. Far from being a fringe issue, a distraction from ‘bread and roses’ issues of material welfare,1 the present article identifies the ‘worker expression’ problem as not merely a manifestation of the age-old conflict between workers and employers, but a contradiction at the heart of labour law itself: between what the article calls the ‘whole self’ approach on the one hand, and the ‘work-self’ approach on the other.
PUBLISHED
Keywords: Employment law; Labour law; Freedom of expression; Human rights; Identities in Transformation; Inclusive Society; Employment and Labour Law; Human rights; Sociolegal Studies